Neutron beam spatial profile at n_TOF using CR-39 nuclear track detectors - Eleme, Z.; Gerovasili, S.; Patronis, N.; Georgali, E.; Ioannides, K. G.; al., et (HNPS Advances in Nuclear Physics, 2019)
N/A